Acute effects of nicotine-free and flavour-free electronic cigarette use on lung functions in healthy and asthmatic individuals. Issue 1 (December 2017) - Boulay, Marie-Ève; Henry, Cyndi; Bossé, Ynuk; Boulet, Louis-Philippe; Morissette, Mathieu
Abstract We designed a crossover and placebo-controlled trial to investigate the impact of a 1-h acute vaping session of nicotine-free and flavour-free e-liquid on the pulmonary functions and respiratory mechanics of healthy and asthmatic individuals. This study shows that a 1-h vaping session of a high-grade and contaminant-free mixture of propylene glycol and glycerol using a commercially available electronic cigarette performed in a controlled environment does not significantly impact pulmonary functions, respiratory mechanics or symptoms in healthy or asthmatic subjects.